THE ANALISIS KEMAMPUAN MEMBACA BUKU NON TEKS MATERI KUKU TERHADAP SISWA KELAS V SEKOLAH DASAR DI SDN BULUSARI SAYUNG DEMAK - Hanik Atul Zahroh; Lina Putriyanti; Bagus Ardi Saputro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the reading ability of non-textbooks on the subject of "Kuku" for fifth-grade students at SDN Bulusari, Sayung, Demak and to obtain an overview of teachers' perceptions of the use of non-textbooks in learning. The method used is descriptive quantitative and qualitative through the distribution of questionnaires to students and teachers. The subjects in this study were 16 fifth-grade students and several teachers involved in the learning process. The results of the student questionnaire showed that the reading ability of non-textbooks is classified as high, with an average score of 46.125 and an average value of 92.25. A total of 9 students are in the very good category, 5 students are in the good category, and 2 students are in the sufficient category. These data indicate that non-textbooks are effective in helping students understand the material visually and contextually. Teacher responses also showed positive results. As many as 90% of teachers stated that non-textbooks attract students' attention, and 80% agreed that the books increase students' interest in reading. Teachers acknowledge the importance of their role in guiding students, especially in understanding vocabulary and scientific terms. However, challenges such as differences in students' understanding levels and technical terms still need to be addressed with appropriate learning strategies. Overall, the non-textbook material "Nails" is considered effective as a supporting medium in improving students' literacy skills in elementary schools.